2013
DOI: 10.3390/s130911899
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Novel Tool for Diagnosing Bile Acid Diarrhoea

Abstract: Bile acid diarrhoea (BAD) is a common disease that requires expensive imaging to diagnose. We have tested the efficacy of a new method to identify BAD, based on the detection of differences in volatile organic compounds (VOC) in urine headspace of BAD vs. ulcerative colitis and healthy controls. A total of 110 patients were recruited; 23 with BAD, 42 with ulcerative colitis (UC) and 45 controls. Patients with BAD also received standard imaging (Se75HCAT) for confirmation. Urine samples were collected and the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 11 publications
2
62
0
1
Order By: Relevance
“…17 However, in the current climate, as none of these tests are routinely available in countries such as the USA, there is interest in the development of a simple, cheap, and readily available biomarker that will help screen for patients that potentially have BAD who can then subsequently be referred on for confirmatory tests. Of these, measurement of serum FGF-19, 18 identification of the primary bile acids cholate and chenodeoxycholate in a single stool sample, 19,20 or detection of volatile organic compounds in a single urine sample (presumed to be a consequence of dysbiosis secondary to elevated levels of colonic bile acids), 21 have all shown initial promising results, but require further work to validate their clinical applicability.…”
mentioning
confidence: 99%
“…17 However, in the current climate, as none of these tests are routinely available in countries such as the USA, there is interest in the development of a simple, cheap, and readily available biomarker that will help screen for patients that potentially have BAD who can then subsequently be referred on for confirmatory tests. Of these, measurement of serum FGF-19, 18 identification of the primary bile acids cholate and chenodeoxycholate in a single stool sample, 19,20 or detection of volatile organic compounds in a single urine sample (presumed to be a consequence of dysbiosis secondary to elevated levels of colonic bile acids), 21 have all shown initial promising results, but require further work to validate their clinical applicability.…”
mentioning
confidence: 99%
“…The Random Forest algorithm (implemented in the R package 'randomForest' , version 4.6-10, R version 3.1.1) (http://cran.ro-project.org/web/ packages/randomForest/index.html) was applied inside the cross-validation loop. From previous studies we have shown that Random Forest provides the best performance for these types of datasets and this was applied here [20][21][22][23][24]. …”
Section: Methodsmentioning
confidence: 99%
“…Patients with significant pelvic radiotherapy induced gastrointestinal side effects have also been identified in this manner [22]. More recent developments include the detection of bile acid diarrhoea (BAD) and distinction of coeliac disease from irritable bowel syndrome by urinary VOC analysis [23,24]. Thus, gas phase biomarkers have been of significant interest as a method of positively diagnosing patients with a wide range of diseases relevant to the field of gastroenterology [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interest arises from the eNoses ability to be non-invasive, point of care, can be produced at price point appropriate for the medical profession and can give a real-time answer. Our research group have previous reported on the efficacy of this approach in detecting and monitoring a variety of gastroenterological and metabolic disorders [3,4].…”
Section: Introductionmentioning
confidence: 99%